2020
DOI: 10.1111/and.13592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin on semen quality characteristics

Abstract: Statins are lipid‐lowering medications widely used to reduce the risk of cardiovascular diseases. Biochemically, they act by decreasing synthesis of cholesterol via inhibiting 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A reductase. Since 1992, various research studies have investigated the effect of statins on semen quality characteristics; however, to date, there is no collective summary to such effect. Here, we have systematically discussed and abridged all research studies published in Scopus, PubMed and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Similarly to those drugs, statins are also capable of affecting semen parameters. Although the use of statins has increased recently, very few data are available concerning their effects on spermatogenesis [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to those drugs, statins are also capable of affecting semen parameters. Although the use of statins has increased recently, very few data are available concerning their effects on spermatogenesis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being well-tolerated, statins cause side-effects such as muscular pain, hepatic enzyme elevation, and an increased risk of diabetes. Another side-effect of statins involves the male reproductive system, although only a few studies to date have investigated this [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the largest studies considered in the review reported a negative effect of statins on semen volume [120,121], sperm concentration [121] and motility [122]. Conversely, in animals, statins were found to ameliorate semen quality characteristics [119], especially in HFD-induced-obesity [123] and in diabetic [124] male rats. Regarding fibrates, a negative effect on reproductive function has been reported in male rats (but not in humans) by a few studies [117,125].…”
Section: Treatment Of Dyslipidemia and Its Impact On Semen Qualitymentioning
confidence: 99%
“…A few studies reported the effect of statins on seminal parameters in human and animal models, while no study has evaluated the impact of fibrates on semen quality in humans. Recently, a systematic review [119] documented that statins exert a strong to minimal negative effect on semen quality. Of note, the largest studies considered in the review reported a negative effect of statins on semen volume [120,121], sperm concentration [121] and motility [122].…”
Section: Treatment Of Dyslipidemia and Its Impact On Semen Qualitymentioning
confidence: 99%